Quantitative Anatomic Comparison of Microsurgical Transcranial, Endoscopic Endonasal, and Transorbital Approaches to the Spheno-Orbital Region. Issue 6 (1st September 2021) - Agosti, Edoardo; Turri-Zanoni, Mario; Saraceno, Giorgio; Belotti, Francesco; Karligkiotis, Apostolos; Rocca, Gregorio; Buffoli, Barbara; Raffetti, Elena; Hirtler, Lena; Rezzani, Rita; Rodella, Luigi Fabrizio; Ferrari, Marco; et al.
Abstract: BACKGROUND: The spheno-orbital region (SOR) is a complex anatomic area that can be accessed with different surgical approaches. OBJECTIVE: To quantitatively compare, in a preclinical setting, microsurgical transcranial approaches (MTAs), endoscopic endonasal transpterygoid approach (EEA), and endoscopic transorbital approaches (ETOAs) to the SOR. METHODS: These approaches were performed in 5 specimens: EEA, ETOAs (superior eyelid and inferolateral), anterolateral MTAs (supraorbital, minipterional, pterional, pterional-transzygomatic, and frontotemporal-orbitozygomatic), and lateral MTAs (subtemporal and subtemporal transzygomatic). All specimens underwent high-resolution computed tomography; an optic neuronavigation system with dedicated software was used to quantify working volume and exposed area for each approach. Mixed linear models with random intercepts were used for statistical analyses. RESULTS: Anterolateral MTAs offer a direct route to the greater wings (GWs) and lesser wings (LWs); only they guarantee exposure of the anterior clinoid. Lateral MTAs provide access to a large area corresponding to the GW, up to the superior orbital fissure (SOF) anteriorly and the foramen rotundum medially. ETOAs also access the GW, close to the lateral portion of SOF, but with a different angle of view as compared to lateral MTAs. Access to deep and medial structures, such as the lamina papyracea and the medial SOF, is offered only by EEA, which exposes the LW and GW only to a limited extent. CONCLUSION: This is the first study that offers a quantitative comparison of the most used approaches to SOR. A detailed knowledge of their advantages and limitations is paramount to choose the ideal one, or their combination, in the clinical setting.